2019
DOI: 10.1111/jocd.12970
|View full text |Cite
|
Sign up to set email alerts
|

The profile of cytokines (IL‐2, IFN‐γ, IL‐4, IL‐10, IL‐17A, and IL‐23) in active alopecia areata

Abstract: Alopecia areata (AA) is a common nonscarring alopecia involving the scalp/body characterized by hair loss without any clinical inflammatory signs. It affects individuals of all age groups and both sexes with a lifetime risk of 1.7%. 1 Patients usually present with wellcircumscribed smooth bald patches ranging from a single patch to complete loss of hair on the scalp (alopecia totalis) or over the entire body (alopecia universalis). 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
2
31
0
2
Order By: Relevance
“…It seems that it is associated with a complex interplay between genetic susceptibility and immune system function 33, 35 . The abnormal levels of pro-inflammatory cytokines (IL-6 and TNF-α) and anti-inflammatory cytokine (IL-10) in AA were confirmed by previous documents 11, 16 . The present meta-analysis discovers a significant link between AA and the inflammatory markers, with SMD for TNF-α (SMD = 2.05, 95% CI 0.98 to 3.13), followed by IL-6 (SMD = 1.57, 95% CI 0.17 to 2.97) and then IL-10 (SMD = -0.22, 95% CI -0.95 to 0.50).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It seems that it is associated with a complex interplay between genetic susceptibility and immune system function 33, 35 . The abnormal levels of pro-inflammatory cytokines (IL-6 and TNF-α) and anti-inflammatory cytokine (IL-10) in AA were confirmed by previous documents 11, 16 . The present meta-analysis discovers a significant link between AA and the inflammatory markers, with SMD for TNF-α (SMD = 2.05, 95% CI 0.98 to 3.13), followed by IL-6 (SMD = 1.57, 95% CI 0.17 to 2.97) and then IL-10 (SMD = -0.22, 95% CI -0.95 to 0.50).…”
Section: Discussionsupporting
confidence: 74%
“…The levels of IL-10 in the serum of healthy subjects were higher than AA patients, but the difference was not significant (SMD = -0.22, 95% CI -0.95 to 0.50). Among six studies that report IL-10 levels in the sera of AA patients, one study shows reduced levels of IL-10 in AA patients compared to healthy controls 17 , one study shows a raised level 16 , and four studies show no significant difference 14,18,25, 26 . There was a significant elevation of IL-6 in the serum of AA patients compared to healthy controls (SMD = 1.57, 95% CI 0.17 to 2.97).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies described an increased serum level of IL-2 in patients with alopecia areata in comparison with healthy controls [ 11 , 22 , 23 , 24 , 25 , 26 , 27 ]. Moreover, higher levels of IL-2 mRNA were detected in peripheral blood mononuclear cells in patients with alopecia areata compared to control subjects [ 24 ].…”
Section: Cytokines In Alopecia Areatamentioning
confidence: 99%
“…A study performed by Gautam et al [ 25 ] revealed a positive correlation between the serum level of IL-2 and the severity of hair loss. Tembhre et al [ 22 ] showed a positive correlation of serum IL-2 level with the total disease duration and the number of hairless patches on the scalp.…”
Section: Cytokines In Alopecia Areatamentioning
confidence: 99%